Metode Drill untuk Meningkatkan Teknik Dasar Menggiring Bola (Dribbling) dalam Permainan Sepakbola pada Siswa Sekolah Sepakbola Putra Zodiac Kabupaten Bojonegoro Usia 13-15 Tahun - Aprianova, Farid; Hariadi, Imam (Performance, 2017)
The purpose of this observation is to improve the basic techniques of dribbling using the drill. This study is a research study sports action. The subjects of this study is the Zodiac, soccer school students Bojonegoro that has 20 students. Data analysis techniques used in the form of quantitative descriptive statistical tests. Data collection techniques in this study using observation. The results the percentage of successful students in the dribble in the game of football after being given the action of cycle 1 and cycle 2, the results on each indicator has been increased from 85% of the leading indicators, the implementation of the (process) 88.33%, and follow through 88.33%. The conclusion of this research is the drill method can improve the basic techniques of dribbling in a Putra Zodiac football school students Bojonegoro.Keywords: drill method, basic techniques dribble, football Abstrak: Tujuan penelitian ini adalah untuk meningkatkan teknik dasar menggiring bola dengan menggunakan metode drill. Penelitian ini merupakan jenis penelitian tindakan olahraga. Subyek penelitian ini adalah siswa sekolah sepakbola Putra Zodiac Kabupaten Bojonegoro yang berjumlah 20 siswa. Teknik analisis data yang digunakan berupa uji statistik deskriptif kuantitatif. Teknik pengumpulan data dalam penelitian ini menggunakan teknik observasi. Hasil observasi diperoleh keberhasilan siswa dalam menggiring bola setelah diberikan tindakan dari siklus 1 dan siklus 2, hasilnya pada tiap-tiap indikator sudah terjadi peningkatan dari indikator awalan 85%, pelaksanaan (proses) 88,33%, dan follow through 88,33%. Kesimpulan yang diperoleh dalam penelitian ini adalah metode drill dapat meningkatkan teknik dasar menggiring bola siswa sekolah sepakbola Putra Zodiac Kabupaten Bojonegoro.Kata kunci: metode drill, teknik dasar menggiring bola, sepakbola